Cyclic deformation and fatigue damage in single-crystal magnesium under fully reversed strain-controlled tension–compression in the [1 0 1¯ 0] direction. (February 2015) - Yu, Qin; Jiang, Yanyao; Wang, Jian
Abstract :  Cyclic deformation and the resulting fatigue are experimentally investigated in single-crystal magnesium subjected to fully reversed strain-controlled tension–compression in the [1 0  1 ¯  0] direction at room temperature. Plastic instability is found near the end of the first detwinning reversal. Twin–twin boundaries and secondary twins are induced by interaction of primary {1 0  1 ¯  2} twins. Microcracks are developed at primary twin boundaries and twin–twin interaction sites. Final fracture is most likely caused by cleavage-cracking on the {1 0  1 ¯  1}–{1 0  1 ¯  2} double twin and shearing fracture on the basal plane.